If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3m + -5) + -1m = -1m + 16 Reorder the terms: 4(-5 + 3m) + -1m = -1m + 16 (-5 * 4 + 3m * 4) + -1m = -1m + 16 (-20 + 12m) + -1m = -1m + 16 Combine like terms: 12m + -1m = 11m -20 + 11m = -1m + 16 Reorder the terms: -20 + 11m = 16 + -1m Solving -20 + 11m = 16 + -1m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add 'm' to each side of the equation. -20 + 11m + m = 16 + -1m + m Combine like terms: 11m + m = 12m -20 + 12m = 16 + -1m + m Combine like terms: -1m + m = 0 -20 + 12m = 16 + 0 -20 + 12m = 16 Add '20' to each side of the equation. -20 + 20 + 12m = 16 + 20 Combine like terms: -20 + 20 = 0 0 + 12m = 16 + 20 12m = 16 + 20 Combine like terms: 16 + 20 = 36 12m = 36 Divide each side by '12'. m = 3 Simplifying m = 3
| (25)+(x+15)=(3x-10) | | Y=-0.414(70)+106.55 | | -1(x+m)=3(x+9)-10 | | 3x+-4=x+2 | | -85=5(1-3x) | | 18-(3-2m)=3(m-5) | | 100[0.03(p+4)]= | | [3x]=-27 | | 6m+2(4-2m)=3(m+4) | | 3/8-5/6= | | 2v^2-11v-40=0 | | -(3w-2)-w=30 | | 3.5+32.1=4.9-10.1x | | 8(2n+5)=6(6n+4)+2 | | Factorx^2+2x+100=0 | | 25x+15=3x-10 | | log(y)=-3log(x) | | 27=-4x+7x-6 | | 15=8+.75x | | 5-3(4-2m)=4(m-3)-3 | | 5m+3(m-2)=6m-12 | | -2-7a=8-5a | | 5(2n+3)=8(6n+1)+4 | | -184=6-8(7-8n) | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 7m-(9-4m)=3(m-11) | | Y+3.9=11.8 | | -184=-8(7-8n) | | Y+3.9=11.8 | | 7m-(9-4m)=3(m-11) | | x^2+4x+2.2=0 | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 |